Effect of irrigation and phosphorus on yield, moisture use and phosphorus uptake of late-sown lentil (Lens culinaris) in calcareous soil - Prasad, U K; Prasad, T N; Mishra, R B (The Indian Journal of Agricultural Sciences, 2012)
In a 4-year field experiment at Pusa (Bihar), late-sown lentil (Lens culinaris Medikus) gave maximum grain-rain yield (1 598kg/ha) with 2 irrigation scheduled through an IW : CPE (irrigation water depth: cumulative pan evaporation) ratio of 0.6 with a total irrigation requirement of 12 cm. Further increase in irrigation to 3 gave similar yield but 1 irrigation significantly reduced the yield. The minimum yield was recorded in the rainfed control. Among levels of P, the yield increased only up to 12.9 kg P/ha. The interaction between irrigation and P was absent. A significant increase in crop-growth rate was recorded up to 2 irrigation and 12.9 kg P/ha. Profile-moisture use by the crop was maximum in 0- Â·30 cm layer than at lower depths. In irrigation and in rainfed, more water was extracted from the lowermost profile (60-90 cm). The uptake of P increased up to 2 irrigations and 12.9 kg P/ha.